Investigation of Flower, Leaf, and Stem Parts of Three Gundelia Species Growth in the Eastern Anatolia Region of Türkiye from a Biochemical Perspective - Yilmaz, Fatih; Turkoglu, Ismail; Kirmizikaya Ozmen, Gorkem; Yuce Babacan, Ebru; Yilmaz, Okkes (Kahramanmaras Sutcu Imam Univ Rektorlugu, 2024)
13 species of Gundelia species plants are endemic in T & uuml;rkiye and are frequently used by the public for both nutrition and medicinal objectives. In this study, three parts (flower, leaf, and stem) of three species of Gundelia ( G.dersim , G.glabra, and G.munzurensis) were biochemically investigated. DPPH and ABTS analyses for antioxidant activity were performed on methanol extracts of plant parts. As a result of both analyses in parallel, the flower part of G.munzurensis had the highest %Inhibition value (DPPH:91.85 +/- 0.78; ABTS:97.38 +/- 0) (P<0.001). In total phenolic (29.09 mg GAE/g) and total flavonoid (5.59 mg CE/g) measurements, the highest amount was found statistically quite significant (P<0.001) in the leaf part of G.munzurensis. Gallic, vanillic, ferulic, romantic, and cinnamic acids, which are phenolic acids and of the flavonoids, rutin, catechin, naringin, and naringenin, were determined in all plant parts. Vitamin D3, alpha-tocopherol, ergosterol, stigmasterol, and beta-sterol were detected in parts of all plant species. While palmitic (16:0), palmitoleic (16:1), stearic (18:0), oleic (18:1), linoleic (18:2), and linolenic (18:3) fatty acids as the main fatty acids were detected in all parts of the three Gundelia species, lauric (12:0), tridecanoic (13:0), myristic (14:0), pentadecanoic (15:0), cis-10-pentadecanoic (15:1), heptadecanoic (17:0), cis-10heptadecanoic (17:1), and eicosanoid (21:0) acids were also identified at different concentrations. Considering the biochemical properties of Gundelia species, it shows that they can be consumed as food and also used pharmacologically.
Keywords: Gundelia; Antioxidant activity; Fatty acids; Vitamins; Phenolic acids